Peranan Komunikasi Petugas Perpustakaan dan Pengguna Perpustakaan dalam Meningkatkan Keberadaan (eksistensi) Perpustakaan pada Perguruan Tinggi Swasta di Kota Banjarmasin - Ahlidah Ahlidah; M. Yunus Jarmie; Zain Noktah Aslie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
Communications officer of library is to represent an interaction process among one with others in the effort to change attide, opinion, behavior between communicator (officer of library) with communicant (consumer of library) by using verbal and nonverbal communications. The research method of the thesis is descriptive or qualitative research. Research place in done at library of private collage In Banjarmasin City those are Library Of UNISKA, STIE PANCASETIA, and STMIK Indonesia Banjarmasin. The goals of this research is to know communications form of any kind of which in using by provider that is librarian, and officer of library to consumer library. The form of communication any kind of which dominating in order to make consumer of libray can exploit amenity of library exsistensi maximaly, any kind of able to make library in order to yield the library which goes forward on continuing. As for informan which in obtaining from the head of library, librarian, officer of library, consumer of library that exist in library of college of private sector in Banjarmasin. Result of research shows that librarians use communications verbal and nonverbal communications. The form of communications officers of library in doing activity everyday using nonverbal communications. The form of communication of library in doing activity everyday using nonverbal communications. Observations, interviu, documentations (triangulation) . The activity everyday dominating comminacations which being used in verbal and nonverbal communications. In fact, library activity yield developed lbrary in continuing with the of library, librarian, officer of library, consumer of library is done continously.